Characterization of glucose‐stimulated insulin release protocols in african green monkeys (Chlorocebus aethiops). Issue 1 (25th October 2018) - Liddie, Shervin; Okamoto, Haruka; Gromada, Jesper; Lawrence, Matthew
Abstract: Background: Management of diabetes remains a major health and economic challenge, demanding test systems in which to develop new therapies. These studies assessed different methodologies for determining glucose tolerance in green monkeys. Methods: Twenty‐eight African green monkeys between 4 and 24 years old underwent single or repeat intravenous glucose tolerance testing (IVGTT), oral glucose tolerance testing (OGTT), and/or graded glucose infusion testing. Results: Geriatric monkeys exhibited glucose intolerance with impaired glucose‐stimulated insulin secretion following IVGTT. Repeat IVGTT and OGTT assessments were inconsistent. Monkeys with low glucose‐stimulated insulin secretion after graded glucose infusion exhibited elevated blood glucose levels. Conclusion: IVGTT and graded glucose infusion protocols revealed differences in glucose tolerance among green monkeys at single time points, including age‐dependent differences suggestive of shifts in pancreatic beta‐cell functional capacity, but care should be applied to study design and the interpretation of data in the setting of longitudinal studies.